2022
DOI: 10.1007/s10585-022-10169-4
|View full text |Cite
|
Sign up to set email alerts
|

FTO mediated ERBB2 demethylation promotes tumor progression in esophageal squamous cell carcinoma cells

Abstract: N6-methyladenosine (m6A) is the most prevalent and internal modification that occurs in the messenger RNAs of eukaryotes. However, knowledge of the impact of these modifications on gene expression regulation remains limited. By using the in vitro MeRIP-seq and RNA-seq assays, we discovered that the mRNA demethylase FTO was significantly up-regulated in esophageal squamous cell carcinoma (ESCC) tissues and cells. Knockdown of FTO drastically suppressed the proliferation, migration, and invasion of ESCC cells. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…It is generally acknowledged that YTHDF1 plays a facilitating role in translation initiation and protein synthesis [ 10 ]. That was true in the study from Zhao et al [ 73 ], which demonstrated that YTHDF1 upregulated the protein level of ERBB2 through recognizing m 6 A-modified ERBB2 mRNA. Conversely, the knockdown of YTHDF1 enhanced the protein level of HSD17B11, which suggested that YTHDF1 decreased the translation efficiency of m 6 A-modified HSD17B11 mRNA [ 74 ].…”
Section: M 6 a Modification And Its Effect On Vari...mentioning
confidence: 88%
See 3 more Smart Citations
“…It is generally acknowledged that YTHDF1 plays a facilitating role in translation initiation and protein synthesis [ 10 ]. That was true in the study from Zhao et al [ 73 ], which demonstrated that YTHDF1 upregulated the protein level of ERBB2 through recognizing m 6 A-modified ERBB2 mRNA. Conversely, the knockdown of YTHDF1 enhanced the protein level of HSD17B11, which suggested that YTHDF1 decreased the translation efficiency of m 6 A-modified HSD17B11 mRNA [ 74 ].…”
Section: M 6 a Modification And Its Effect On Vari...mentioning
confidence: 88%
“…Thus, the A allele of rs5746136 in SOD2 was associated with a reduced risk of bladder cancer [ 57 ]. m 6 A could deposit on various type of RNA, such as coding RNA and non-coding RNA, participate in all steps of RNA metabolism and post-transcriptionally regulate the expression of the gene ( Table 1 ) [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 ].…”
Section: M 6 a Modification And Its Effect On Vari...mentioning
confidence: 99%
See 2 more Smart Citations
“…In the TCGA cases, we observed a significant negative correlation between ERBB2 DNA methylation and gene mutation at the promoter region. Integrating gene expression and DNA methylation data obtained from gene mutation analysis were compared with DNA methylation analysis to identify genes that were significantly altered in DNA methylation ( 22 ).…”
Section: Methodsmentioning
confidence: 99%